Maternal mental health and nutritional status of six-month-old infants - Bruna Kulik Hassan; Guilherme Loureiro Werneck; Maria Helena Hasselmann (Universidade de São Paulo, 2016)
ABSTRACT OBJECTIVE To analyze if maternal mental health is associated with infant nutritional status at six month of age. METHODS A cross-sectional study with 228 six-month-old infants who used primary health care units of the city of Rio de Janeiro, Southeastern Brazil. Mean weight-for-length and mean weight-for-age were expressed in z-scores considering the 2006 World Health Organization reference curves. Maternal mental health was measured by the 12-item General Health Questionnaire. The following cutoff points were used: ≥ 3 for common mental disorders, ≥ 5 for more severe mental disorders, and ≥ 9 for depression. The statistical analysis employed adjusted linear regression models. RESULTS The prevalence of common mental disorders, more severe mental disorders and depression was 39.9%, 23.7%, and 8.3%, respectively. Children of women with more severe mental disorders had, on average, a weight-for-length 0.37 z-scores lower than children of women without this health harm (p = 0.026). We also observed that the weight-for-length indicator of children of depressed mothers was, on average, 0.67 z-scores lower than that of children of nondepressed women (p = 0.010). Maternal depression was associated with lower mean values of weight-for-age z-scores (p = 0.041). CONCLUSIONS Maternal mental health is positively related to the inadequacy of the nutritional status of infants at six months.